BOLD activation on the groundside of figures: More suppression of grounds that competed more for figural status. (January 2023) - Cacciamani, Laura; Skocypec, Rachel M.; Flowers, Colin S.; Perez, Diana C.; Peterson, Mary A.
Abstract: A fundamental aspect of object detection is assigning a border to one (figure) side but not the other (ground) side. Figures are shaped; grounds appear shapeless near the figure border. Accumulating evidence supports the view that the mechanism of figure assignment is inhibitory competition with the figure perceived on the winning side. Suppression has been observed on the groundside of figure borders. One prediction is that more suppression will be observed when the groundside competes more for figural status. We tested this prediction by assessing BOLD activation on the groundside of two types of stimuli with articulated borders: AEnov and AEfam stimuli. In both stimulus types, multiple image-based priors (symmetry, closure, small area, enclosure by a larger region) favored the inside as the figure. In AEfam but not AEnov stimuli, the figural prior of familiar configuration present on the outside competes for figural status. Observers perceived the insides of both types of stimuli as novel figures and the outsides as shapeless grounds. Previously, we observed lower BOLD activation in early visual areas representing the grounds of AEfam than AEnov stimuli, although unexpectedly, activation was above baseline. With articulated borders, it can be difficult to exclude figure activation from ground ROIs. Here, our ground ROIs better excluded figure activation; we also added straight-edge (SE) control stimuli and increased the sample size. In early visual areas representing the grounds, we observed lower BOLD activation on the groundside of AEfam than AEnov stimuli and below-baseline BOLD activation on the groundside of SE and AEfam stimuli. These results, indicating that greater suppression is applied to groundsides that competed more for figural status but lost the competition, support a Bayesian model of figure assignment in which proto-objects activated at both low and high levels where image features and familiar configurations are represented, respectively, compete for figural status.